Gaps in health research related to sex work: an analysis of Canadian health research funding. Issue 1 (1st January 2023) - Bungay, Vicky; Guta, Adrian; Varcoe, Colleen; Slemon, Allie; Manning, Eli; Comber, Scott; Perri, Melissa
ABSTRACT: Public health is tasked with addressing the urgent global priority of promoting the health and human rights of adults engaged in sex work and research is critical to support this endeavor. 'What' is studied, 'how' research is done, and 'who' is centered in this research is reflected in how research funding is allocated. In this article, we interrogate funding allocation for sex work-related health research in Canada. Drawing on critical perspectives aimed at illustrating how stigma operates in society, we examine operating grants (N = 64) awarded by the federal health research funding agency between 2003 and 2020. We find that sex workers' health is problematized disproportionately in a street marketplace context that centers on HIV and sexually transmitted infections. Limited work attends to the socio-structural context of sex work and instead perpetuates stigmatizing narratives about sex work. Public health intervention studies are rare, presenting a barrier for implementing and evaluating evidence-based health promotion strategies. Notably, the research projects were conducted by a small number of highly networked, geographically clustered researchers, illustrating gaps in research that considers the complexity of sex work. We propose that it is essential to consider funding as a process that may be limiting the range of health issues being addressed and privileging a small community of researchers, which can inadvertently serve to worsen health inequities among some sex work communities. Researchers and funding bodies may draw on this analysis to inform a research agenda that meaningfully supports the health, safety, and well-being of sex workers in Canada and globally.